PENGARUH KOMPETENSI GURU TERHADAP KINERJA GURU MELALUI KEPUASAN KERJA GURU SEKOLAH MENENGAH PERTAMA KABUPATEN BOMBANA - Siti Rahma; Nurwati Nurwati; Eliyanti Agus Mokodompit (Pascasarjana Universitas Halu Oleo, 2022)
The purpose of this study was to determine and analyze the effect of teacher competence on job satisfaction of junior high school teachers in Bombana Regency. Teacher job satisfaction on the performance of junior high school teachers in Bombana Regency. Teacher competence on the performance of junior high school teachers in Bombana Regency and teacher competence on teacher performance through job satisfaction for junior high school teachers in Bombana Regency.The results of this study indicate that teacher competence has a positive and significant effect on teacher satisfaction at Bombana Regency Junior High Schools. This means that the better the increase in competence, it will increase teacher job satisfaction. Teacher satisfaction has a positive and significant effect on the performance of junior high school teachers in Bombana Regency. This means that the better the increase in teacher job satisfaction, the better the teacher's performance. Teacher competence has a positive and significant effect on the performance of junior high school teachers in Bombana Regency. This means that the better the increase in competence, the better the performance of teachers. Teacher competence has a positive and significant effect on teacher performance through the satisfaction of junior high school teachers in Bombana Regency. This means that teacher competence is able to improve teacher performance through mediation of teacher job satisfaction..